Controlling Risks Through Ergonomics Participatory In Industry Of Processed Meat Products Certified Halal - Wahyu Susihono; Asep Ridwan; A. Ali Alhamidi (International Journal of Supply Chain Management, 2021)
The halal certified processed meat industry in Banten province reaches 147 industries spread across eight districts / cities in Banten Province. Evaluation of the HAS-2300 implementation has been carried out periodically, but there are still various weaknesses that result in the company's performance being not optimal. Risk control has also been implemented to anticipate various contaminants and activities that may harm employees, but there are still errors in implementing work procedures. Risk control through participatory ergonomics is needed to find the most critical point in the halal meat processing industry. Respondents in this study were determined based on purposive sampling technique. The results showed that the greatest risk comes from social-technical factors, namely that humans are the main factor at the critical point of materials. Although the process of slaughter has been assisted by the adoption of technology, the existence of humans is not replaced by machines. Animal slaughter techniques are the key to meeting the critical point of meat products